The paradox of progress : economic change, individual enterprise, and political culture in Michigan, 1837-1878 - Hershock, Martin J., 1962- (Ohio University Press, 2003)
"Martin Hershock traces the ways in which all classes in the state of Michigan found themselves simultaneously attracted to the enticements of the new world of the market and repulsed by its excess and instability. The Paradox of Progress is a study of Michigan history and politics as well as an analysis of the factors underlying the history of the GOP and its evolution from the party that supported the antislavery movement, free soil, free labor, and Lincoln the Rail-Splitter into the party of Mark Hanna, J.P. Morgan, and William McKinley."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved